Price Elasticity of Water Demand in a Small College Town: An Inclusion of System Dynamics Approach for Water Demand Forecast. Issue 7 (January 2014) - Dhungel, Ramesh; Fiedler, Fritz
The relationship between water demand and pricing using the price elasticity of water demand in the City of Pullman, Washington, between 2000 and 2006 shows that the current amount of water depletion is not sustainable. Three different economic scenarios were developed by altering variables in regression equations to investigate the influence of individual variables on estimating the final price elasticity of water demand. Single-family households, total residential households, and total population water use of the City of Pullman, Washington were the three different economic scenarios developed for calculating the price elasticity of water demand. The regression results show that the price elasticity of marginal price is inelastic. The exponents for median household income, fixed price, and precipitation had the expected signs in all applied scenarios. An economic model based on the regression equation of price elasticity was developed using a systems dynamic approach. The economic model projected a decline in water demand when the independent variables were assumed to grow linearly over the coming 25 years. When the household size with higher elasticity values was excluded from the regression equation, the developed economic model was able to forecast reasonable water demand. The time series data with exact service connections are recommended to reduce the uncertainty in the computation of the price elasticity of water demand. Further sensitivity analysis is recommended to understand interrelationship of water demand and pricing from the developed economic model using system dynamics approach.